Dairy Farmers’ Intention to Use High-Precision Area-Level Weather Warning Technology in Dairy Farms in Thailand Through an Application on Mobile Phones - Rajchamaha, Kittichai; Makararpong, Davids (International Journal of Interactive Mobile Technologies (iJIM), 2023)
Data from information technology has been crucial in advancing the agricultural and livestock industries, especially for Thai dairy farms located in tropical regions where sudden weather changes can occur. This study uses the technology acceptance model (TAM) and the innovation diffusion theory (IDT) to predict the Thai dairy farmers’ intention to use a high-precision area-level weather warning technology through a mobile phone application. A questionnaire was collected from dairy farm owners in Thailand’s central and northeastern regions, and the data was analyzed using stepwise multiple linear regression. The main factor influencing the acceptance of this technology was its compatibility with existing technology, and it needed to be available on mobile phones for instant access. The role of technology had to provide dairy farmers with information for decision-making, especially during extreme weather conditions, to mitigate potential damage. Training sessions and workshops on the implementation of this technology were necessary, and young farmers could share content on social media to promote its benefits. Service providers should set up call centers to help dairy farmers make decisions. This study identifies factors that can increase farmers’ intentions to use digital technology. By addressing these factors, the adoption of technology can improve the efficiency and productivity of dairy farming in Thailand.